2020
DOI: 10.1111/aos.14631
|View full text |Cite
|
Sign up to set email alerts
|

Progression of macular atrophy in patients undergoing anti‐vascular endothelial growth factor therapy for neovascular age‐related macular degeneration

Abstract: Purpose To assess differences in the progression of macular atrophy (MA) between neovascular age‐related macular degeneration (AMD) subtypes and to identify the risk factors associated with the foveal involvement among patients with MA undergoing long‐term anti‐vascular endothelial growth factor (VEGF) treatment. Methods Eighty eyes of 80 patients with neovascular AMD who developed incident MA following anti‐VEGF therapy were retrospectively included. Macular atrophy (MA) was quantified using autofluoresence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…It has been hypothesized that sub-RPE neovascularization in nAMD represents a compensatory response to hypoxia that limits ischemia and further damage to the RPE [29][30][31]. In support of this, previous studies have associated type 1 (or occult) MNV with lower rates of geographic atrophy, macular atrophy progression, and retinal scarring compared with other MNV subtypes [31][32][33][34]. Similar to type 1 MNV, the presence of SRF has also been associated with lower rates of atrophy and better long-term vision outcomes [30,[35][36][37][38], and the phase 4 FLUID study (Comparison of Treatment Regimens Using Ranibizumab: Intensive [Resolution of Intra-and Subretinal fluid] Versus Relaxed [Resolution of Primarily Intraretinal Fluid]) recently showed that BCVA gains in patients treated with a ranibizumab treatand-extend regimen that tolerated some SRF were comparable with those receiving a treat-and-extend regimen that resolved all SRF [39].…”
Section: Discussionmentioning
confidence: 95%
“…It has been hypothesized that sub-RPE neovascularization in nAMD represents a compensatory response to hypoxia that limits ischemia and further damage to the RPE [29][30][31]. In support of this, previous studies have associated type 1 (or occult) MNV with lower rates of geographic atrophy, macular atrophy progression, and retinal scarring compared with other MNV subtypes [31][32][33][34]. Similar to type 1 MNV, the presence of SRF has also been associated with lower rates of atrophy and better long-term vision outcomes [30,[35][36][37][38], and the phase 4 FLUID study (Comparison of Treatment Regimens Using Ranibizumab: Intensive [Resolution of Intra-and Subretinal fluid] Versus Relaxed [Resolution of Primarily Intraretinal Fluid]) recently showed that BCVA gains in patients treated with a ranibizumab treatand-extend regimen that tolerated some SRF were comparable with those receiving a treat-and-extend regimen that resolved all SRF [39].…”
Section: Discussionmentioning
confidence: 95%
“… 1 3 Type 3 CNV was associated with an increased risk of MA and type 2 CNV with an increased risk of SRFi, which has been confirmed in previous reports. 1 , 9 , 10 , 19 …”
Section: Discussionmentioning
confidence: 99%
“… 6 8 Older age, presenting VA, and type of choroidal neovascularization (CNV) may predict risk of progression to MA and SRFi under treatment more strongly than treatment strategy and frequency. 1 , 9 , 10 Few studies, if any, have investigated whether there is any other mechanism that causes visual loss in eyes with nAMD independently of these features. Here, we tested the hypothesis that eyes with nAMD treated with VEGF inhibitors continue to lose vision through unknown mechanisms, even if they do not develop SRFi or MA.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present study involving only type 3 MNV, the incidence of macular atrophy was not affected by the presence of SRF. This finding could be associated with the higher incidence and faster growth of macular atrophy in patients with type 3 MNV compared to other types of MNV 5 , 11 , 27 . Type 3 MNV is characterized by a thin choroid and impaired choriocapillaris perfusion, which causes vulnerability to RPE atrophy 5 , 28 .…”
Section: Discussionmentioning
confidence: 92%